Marxist economic theories and the Great Recession - Palludeto, Alex Wilhans Antonio; Andrade, Rogerio P. de (Brazilian Journal of Political Economy, 2017)
This review paper examines some of the main Marxist-inspired interpretations of the Great Recession that were published in the form of books. From the broad set of publications on the subject, the following works were analyzed: The Great Financial Crisis, by John Bellamy Foster and Fred Magdoff (2009); The Enigma of Capital, by David Harvey (2011), originally published in 2010; The Crisis of Neoliberalism, by Gérard Duménil and Dominique Lévy (2011); and The Failure of Capitalist Production, by Andrew Kliman (2012). It is argued that the Marxist debate about the ultimate causes of the Great Recession can be systematized from the following cleavage: 1) on the one hand, the authors who attribute the turbulence to the specific political/economic/institutional form assumed by the capitalist system over the last decades; 2) on the other hand, those who interpret the recent crisis as a manifestation of capitalist dynamics in general - and not the particular form that it supposedly assumes. While Foster & Magdoff (2009), Harvey (2011) and Duménil & Lévy (2011) belong to the first group, Kliman (2012) is a representative of the second strand. JEL Classification: E11; G01.